A research framework to isolate visuospatial from childhood motor coordination phenotypes. Issue 4 (2nd October 2019) - Poletti, Michele
ABSTRACT: Clinicians acknowledge the presence of developmental cognitive phenotypes mainly characterized by a specific visuospatial impairment in presence of intact verbal functioning (usually referred as Nonverbal Learning Disability: NLD) since many decades, without providing sufficient empirical evidence supporting their nosological validity and inclusion in current diagnostic manuals. This contribution suggests that the goal of including NLD in future diagnostic manuals could be achieved only be the demonstration of the validity of this hypothesized clinical category. Considering the blind spot of empirical literature represented by the differential diagnosis of NLD, this issue should the primary focus of empirical research supported by a renewed interest on NLD. Both neurophysiological and clinical evidence suggest that the differential diagnosis and the related empirical comparison should be primarily settled with Developmental Coordination Disorder, looking for the possible identification of children presenting a visuospatial impairment in absence of severe motor coordination impairment. In conclusion, further studies are needed to support the validity of NLD as valid diagnostic category to be included in future revisions of diagnostic manuals.